Unlocking plant defense: Exploring the nexus of biochar and Ca2+ signaling - Rubab Sarfraz; S.V.G.N. Priyadarshani; Ali Fakhar; Muhammad Israr Khan; Zohaib Ul Hassan; Pil Joo Kim; Gil Won Kim (Plant Stress)
The interaction between biochar application and calcium ions (Ca2+) in plants, in terms of activating plant defense mechanism would be useful to improve plant resilience and sustainable agriculture. This review aims to highlight the possible connection between biochar-induced changes in soil physicochemical properties, microbial interactions, and Ca2+ dynamics, ultimately leading to promote the plant defense mechanisms. We are also interested to discuss the role of Ca2+ signaling in coordinating plant responses to various biotic and abiotic stresses such as pathogen and insects attacks, cold or heat stress and drought stress as well as how Ca2+ fluxes, calcium-binding proteins, and ion channels are influenced by biochar application in the soil environment. Furthermore, we examine the impact of biochar on plant Ca2+ signaling pathways and how it can prime defense genes and strengthen call wall barriers to improve plant immunity. Despite significant progress, there is a need for interdisciplinary collaboration to fully sort out the mechanism of Ca2+ signaling in plants and induction of Ca2+ ions by biochar induction in soil environment. Advanced imaging techniques, proteomics and omics approaches could be helpful to unlock the complex interaction between biochar application and Ca2+ signaling. Overall, this review contributes substantially to the literature by describing the relationship between biochar and Ca2+ signaling and providing insights into novel approaches for enhancing plant defense mechanisms and development of sustainable agricultural solutions.